DETERMINAN PENERIMAAN PAJAK PERTAMBAHAN NILAI - Putri, Adeline Kezia; Pradipta, Arya (E-Jurnal Akuntansi TSM, 2024)
The purpose of this research is to obtain empirical evidence of the effect of the Self Assessment System, Tax Audit, Tax Collection, Number of Taxable Entrepreneurs, Number of e-billings and Number of e-filings on value added tax revenue at KPP Pratama Tanjung Pandan. The population in this study were all corporate taxpayers at KPP Pratama Tanjung Pandan. The sampling technique in this study used purposive sampling technique so that the samples are taken based on certain criteria. The criteria used are corporate taxpayers who are registered and active as taxable entrepreneurs at the Tanjung Pandan KPP Pratama during the 2015-2022 period. The research carried out is a time series study for 8 years with monthly data units, so the total number of samples was 96. The results of this research show that 2 (two) independent variables, Self Assessment System and e-billing have a positive effect on value added tax revenues at KPP Pratama Tanjung Pandan. Meanwhile, the other 4 (four) independent variables are tax audit, tax collection, taxable entrepreneurs, and e-filing have no effect on value added tax revenue at KPP Pratama Tanjung Pandan.